Total Productive Maintenance (TPM) untuk Mesin Crawler Crane pada PT. X - Antonia Jessica Tedja; Felecia Felecia (Jurnal Titra, 2021)
This research is conducted to analyse about Total Productive Maintenance (TPM) at PT. X. PT. X itself is a construction company since 1994. This research focussed on the case study of crawler crane machines, especially service cranes owned by the company. PT. X said that the problem they face right now is sudden malfunction of the crawler crane that will certainly disrupt the pilling process. The company tries to increase the effectiveness of the machine by implementing TPM. The case study on the service crane will be analysed/calculated using Overall Equipment Effectiveness (OEE), which is one of the evaluation tools for TPM. OEE can show the productivity percentage of the crawler crane machine. The calculation of Six Big Losses also needs to be done to find out what losses have influenced the crawler crane effectiveness’ the most. This study provides recommendations using the 8 pillars of TPM aim to solve the most influential losses.